2022
DOI: 10.1016/j.ebiom.2022.103833
|View full text |Cite
|
Sign up to set email alerts
|

Seizure modulation by the gut microbiota and tryptophan-kynurenine metabolism in an animal model of infantile spasms

Abstract: Background The infantile spasms syndrome is an early-onset epileptic encephalopathy presenting in the first 2 years of life, often with severe developmental consequences. The role of the gut microbiota and metabolism in infantile spasms remains unexplored.Methods Employing a brain injury neonatal rat model of infantile spasms intractable to anticonvulsant medication treatments, we determined how the ketogenic diet and antibiotics affected specific microbial communities and the resultant circulating factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 68 publications
0
37
1
Order By: Relevance
“…At present, the mechanisms underlying the beneficial impacts of the diet are unclear. However, recent work implicates the gut microbiota, the trillions of microorganisms that inhabit our intestines as playing a fundamental role [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, the mechanisms underlying the beneficial impacts of the diet are unclear. However, recent work implicates the gut microbiota, the trillions of microorganisms that inhabit our intestines as playing a fundamental role [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Employing antibiotics and fecal microbiota transfer into germ-free mice, Olson and colleagues [ 7 ] demonstrated that the seizure-reducing effects of the diet are dependent on the gut microbiota in two rodent models of epilepsy. Likewise, gut-microbiome-based manipulations, including the KD, antibiotics, and probiotics, have been shown to suppress seizures (spasms) in a neonatal brain injury rat model of infantile spasms [ 3 , 8 , 9 ]. Similar to the abovementioned study, the protective impacts of the diet could also be transferred to another animal by fecal transplant alone, showing the gut-based dependency of the treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Recently, tantalising discoveries have suggested that such modifications could target the gut microbiome, an apparent key player in the causal chain leading from the ketogenic diet to anti-seizure changes in the brain. 2 Two research papers by Mu and colleagues published recently in eBioMedicine 3 , 4 make valuable progress in the direction of ketogenic diet optimization, in the specific case of infantile spasms syndrome. Their findings are particularly noteworthy for their direct clinical implications, but also advance our understanding of particular mechanisms of the ketogenic diet in infantile spasms.…”
mentioning
confidence: 99%
“…The first of these publications 4 reveals that a variety of mechanistically-overlapping gut microbiome-based manipulations are capable of suppressing infantile spasms in the brain injury neonatal rat model. These manipulations included the ketogenic diet itself (observed here and elsewhere to significantly adjust the microbiome), a 3-day broad spectrum oral antibiotic regime (both together with and independently of the ketogenic diet), and fecal microbial transplants from ketogenic diet-fed rats.…”
mentioning
confidence: 99%